THE ROLE OF TEACHER IN EFFECTIVE LEARNING (Proceedings of International Educators Conference, 2023)
This study aims to describe the role and function of teachers in enhancing effective learning, inhibiting resisting solutions to teacher obstacles in carrying out the roles and functions of teachers. Teachers are defensible the most important members of our society. They give children purpose, set them up for success as citizens of our world, and inspire in them a drive to do well and succeed in life. The children of today are the leaders of tomorrow, and teachers are that critical point that makes a child ready for their future. If we could look at the development of the school and the teacher's role in historical terms, we see that the function and the role of the teacher have changed as society has changed, along with the running of the school. All teachers are classroom managers who reinforce appropriate behavior, measure student learning and create inclusive learning environments. Some teachers work primarily with student populations needing extra support, such as special education students or English Language Learners.